Oracle Database: An In-Depth Analysis of the DBMS That Dominates the Corporate World - Carr, Caroline Nunes; Silva, Eduardo de Vasconcelos; Lima, Gustavo Casanova Oliveira; Carr, Renato Ferreira; Braga, Tomas Robyson da Cruz (Research, Society and Development, 2023)
In this article, a thorough analysis of Oracle Database, one of the most widely used database management systems (DBMS) in the corporate world, is performed in order to evaluate its security, performance and adaptability in relation to other systems available in the market. The methodology employed is the narrative bibliographic review, based on secondary sources such as scientific articles, technical reports, and case studies. The text begins with a brief introduction to the DBMS, followed by a discussion of its forms of insertion in the market, such as high availability and support for multiple platforms. The composition explores its core functions and advantages, emphasizing the enterprise innovation that Oracle Database brings to companies that embrace it in their operations. In addition, success stories of companies that have opted for Oracle Database are presented, highlighting its effectiveness in the management of sensitive and complex data. Finally, adoption perspectives are discussed in the corporate environment, for the future of database technology, considering the importance of Oracle Database in a scenario in constant transformation and improvement.